Ethnolinguistic-based interactive digital storytelling for cultural literacy development in primary education - Andarini Permata Cahyaningtyas; Sukardi Sukardi; Panca Dewi Purwati; Yulina Ismiyanti (Jurnal Ilmiah Pendidikan Dasar, 2026)
Despite the growing focus on digital literacy training, there is still little empirical research combining ethnolinguistics with interactive digital storytelling in elementary school. To improve students' cultural literacy, this study proposes and assesses an innovative teaching strategy that integrates ethnolinguistic aspects of farming culture into interactive digital storytelling. Before being used in elementary classrooms, the digital media were created based on the needs analysis and verified by specialists using the design-based research framework ADDIE. Pre- and post-tests and instructor evaluations were used to gauge students' cultural literacy, and the results were analysed quantitatively using normality tests and the Wilcoxon test. The data reveal that the ethnolinguistic-based interactive storytelling greatly increased students’ grasp of local farming culture and their awareness of linguistic diversity, demonstrating meaningful learning gains following the intervention. Student and teacher responses also showed that the video is practical for elementary school students. These results add empirical evidence for the effectiveness of culturally grounded digital storytelling in primary school and show its potential for enhancing ethnolinguistics-informed literacy pedagogy and culturally responsive learning in multilingual contexts.